The impact of different uses of the Internet on students’ performance progression throughout primary education. - Ladrón de Guevara Rodríguez, Maria; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Springer, 2023)
The present research analyses the impact that the time spent on the Internet by primary school (3rd and 6th grade) students may have on their academic progression in terms of test scores. In order to go beyond a correlational analysis, we have applied a time fixed-effects estimation using a recent longitudinal database of 15,974 students from the Spanish region of the Canary Islands. Our results show that, in general, an increasingly frequent use of the Internet has a negative influence on students’ academic achievement progression, with higher use of instant messaging applications being particularly linked to girls’ poorer mathematics academic performance progression. This negative influence may be a consequence of replacing time to academic activities (e.g., reading books or homework) with time using the Internet, which can also ultimately lead students to adopt unhealthy study habits that can affect their future academic success. Furthermore, we find that there is not a negative impact of playing videogames on the mathematics competence, as the development of spatial-visual (digital) skills possibly counterbalances the negative influence of time substitution between academically oriented tasks and the Internet.
https://openpolicyfinder.jisc.ac.uk/id/publication/16998
Keywords: Rendimiento académico; Internet en la enseñanza; Enseñanza primaria; Educación - Modelos matemáticos; Internet uses; Student’s performance; Fixed-effects; Primary education